Estudio socio-económico de los productores de maíz en el recinto La Lola Grande, cantón Montalvo - Córdova Guerrero, Diana Elena (2019)
The work was carried out in the La Lola Grande area of the parish La Esmeralda of the Montalvo city, through a survey of corn producers and analyzing the descriptive results of the results, with the aim of diagnosing the socio-economic real status of maize-producing farmers. Their educational instruction corresponds to 56% primary education, secondary education 35% and 9% kept their studies in universities. 32% of farmers spend their time producing maize, 40% on cocoa, rice 20% and banana 8%, with a second place to the crop under study. All farmers interviewed ownland greater than 2 Ha, and 70% of them non-rotation of crops, while 30% rotations sowing rice and maize according to the season. They have a base of US$400 as a monthly basis, which makes it easier to obtain in private financial institutions (80%) state (20%). 90% of maize producers in the area remain firmly in maize cultivation, with a very profitable crop according to investment, while 10% of maize producers practice it so as not to have their in barbecho land